A5_9 Falling in the Rain - Keany, Connor; Graham, Thomas; Kaiser, Felix; Newland, Rhys; Pankhania, Kishen (Physics Special Topics, 2022)
The goal of this paper was to investigate what effects rain might have on the terminal velocity of a person. By considering the exchange of momentum from collisions with raindrops and the increase of mass due to wet clothes, it was found that falling in the rain increased a persons terminal velocity by 0.8%